If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -5 = -20 Reorder the terms: -5 + 3p = -20 Solving -5 + 3p = -20 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3p = -20 + 5 Combine like terms: -5 + 5 = 0 0 + 3p = -20 + 5 3p = -20 + 5 Combine like terms: -20 + 5 = -15 3p = -15 Divide each side by '3'. p = -5 Simplifying p = -5
| 2.4x=8.64 | | 7x^2+16x-15= | | 72-6x=21x+24 | | 7x+1=-35 | | 3x+47=-5 | | 49r(2)+21r=-2 | | 1-6x=-35 | | (2/3)-0,2x=(1/3)-0,5x | | 2c+6=-1-3c | | 70+30=2x | | 3n^2+6n-24=0 | | 5m^2-50m+125=0 | | 6-(1/3)x=2x-3 | | 5(a-8)+14=3(a-6) | | 5m+9=4 | | 5-2x=x+6 | | -6x-3(2x-18)=186 | | -50=5x+4(-3x-2) | | 5x*3y= | | a/2+b/2=c/2 | | 4p^2-4p-48=0 | | -8-9=-3(d+3)-5d | | 2(3x-4)=2(21x+16) | | -5x+2(-2x-11)=-76 | | 2x+3.4=8 | | 2x(3x+1)=28 | | xy+30y-30=0 | | 5x^(1/3)-x^(2/3)-54=0 | | -8r-7=24 | | 20(-1/2) | | 1/5(2x+9)=2(1-2x)+13 | | 190=-7x-5(5x-6) |